The Role of Interdisciplinary Collaboration in Combating Infection in Health Facilities: A Systematic Review - Alkhorem, Ibrahem Mohammed; Al khreim, Ali Salem Saleh; Alabbas , Saleh Mana Musleh; Alkhureem , Ali Mohammed Salem; Alkhorem, Salem Mohammed; Al khurym , Ali Mohammad Saleh; Alkhuraym , Hussain Hamad Ali; Alyami, Salem Hamad; Al Alghaber, Majed Mahdi Saleh; Al khzayam, Mabkhwt Mohammed M (Journal of Ecohumanism, 2024)
Infection control in health facilities is critical for patient safety, with interdisciplinary collaboration emerging as a significant factor in reducing infection rates. This systematic review examines the role of collaborative efforts among healthcare professionals, including doctors, nurses, pharmacists, and laboratory technicians, in combating infections within healthcare settings. Utilizing databases such as PubMed, Scopus, and Cochrane Library, 32 studies published between 2014 and 2024 were analyzed, focusing on collaboration models, infection control outcomes, and the barriers and facilitators of teamwork. The findings reveal that interdisciplinary collaboration enhances adherence to infection control protocols, fosters clear communication, and improves overall compliance with hygiene practices. Key benefits include reduced healthcare-associated infections, faster response to infection outbreaks, and improved patient outcomes. However, challenges such as communication gaps, unclear role definitions, and limited resources hinder effective collaboration. The review suggests that structured interdisciplinary practices, supported by training, leadership engagement, and integrated technology, are essential for effective infection control. These insights can guide healthcare administrators and policymakers in strengthening infection prevention strategies. Future research should focus on evaluating the long-term impact of collaboration on infection rates and examining the roles of specific professionals in infection control.